2017
DOI: 10.1097/mpg.0000000000001580
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Low Seroimmunity to Hepatitis B Virus in Children With Inflammatory Bowel Disease

Abstract: Nearly two-thirds of pediatric patients with IBD have low titers against hepatitis B virus. Titers were highest in the younger patients. No patient-specific variable, such as the use of immunosuppressants, appeared to influence these low titers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 37 publications
3
26
3
Order By: Relevance
“…Second, the dose of hepatitis B vaccine varies in pediatric studies. Urganci et al [12] administered 20 µg hepatitis B vaccine, while three other studies, including ours, used a 10-µg dose [10,11]. In all studies, full HBV vaccination was defined as 3 doses; however, in a study by Moses et al, "three or more doses" were considered as the full series [11].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Second, the dose of hepatitis B vaccine varies in pediatric studies. Urganci et al [12] administered 20 µg hepatitis B vaccine, while three other studies, including ours, used a 10-µg dose [10,11]. In all studies, full HBV vaccination was defined as 3 doses; however, in a study by Moses et al, "three or more doses" were considered as the full series [11].…”
Section: Discussionmentioning
confidence: 95%
“…First, we measured the antibody level approximately 14 years after vaccination. In the Urganci et al study [12], the period after vaccination was 4 weeks, and the time was not reported in studies by Watts et al [10] and Moses et al [11]. It is documented that in immunocompetent individuals who are fully vaccinated against HBV, protective serologic titers may persist for more than 20 years, and no booster dose is recommended [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, it has been reported that 6-TG can combat Middle East respiratory syndrome coronavirus infection by augmenting interferon responses (Cheng et al, 2015) and it has also reported that Simian virus 40 DNA replication is antagonized by 6-TG (Maybaum et al, 1987). Interestingly, it was reported that vaccinated IBD patients had lower titers of hepatitis B surface antibody (HBsAb), which might be influenced by the use of immunosuppressants including 6-TG (Watts et al, 2017).…”
Section: Discussionmentioning
confidence: 99%